Ästhetische Theorie - Adorno, Theodor W. 1903-1969 (Frankfurt am Main Suhrkamp taschenbuch wissenschaft, 1998)
Aesthetic Theory is the penultimate draft of Adorno's major text on aesthetics, published in an edition prepared by Gretal Adorno and Rolf Tiedemann in the year following Adorno's death. Along with Negative Dialectics and a projected book on ethics, Adorno intended Aesthetic Theory to ?show what I have to throw into the scale? (Adorno 1997, p. 459). Aesthetic Theory is the final summary of a lifetime of philosophical and sociological reflection on the arts. Yet because it is only a penultimate draft and, as its editors note, it is not the work that Adorno himself would have sent to the printers (Adorno 1997, p. 459). This fact, along with a first translation that lent itself too readily to easy ...